2008
DOI: 10.2320/matertrans.mer2008140
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microstructure Evolution on the Elevated Temperature Mechanical Properties in Mg-Sn-Ca System

Abstract: The effect of microstructural evolution on the creep properties in Mg-Sn-Ca system has been investigated. As-cast microstructure of MgSn-Ca alloy consists of two or three phases depending on the Ca/Sn ratio, i.e. Mg 2 Sn, CaMgSn and Mg 2 Ca phases. Ternary CaMgSn phase has two types of morphology by its pseudo hyper-eutectic reaction with -Mg; coarse rod-like primary or feather-like eutectic phase. Primary solidified CaMgSn phase exhibit negative effect on the tensile properties in spite of its high thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…5 shows the SEM images of the as-cast experimental alloys. Similar to the previous investigations [16,17], the coarse needlelike primary CaMgSn phases and the feather-like eutectic CaMgSn phases are clearly observed in the ternary Mg-3Sn-2Ca alloy (see Figs. 4 and 5a and b).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…5 shows the SEM images of the as-cast experimental alloys. Similar to the previous investigations [16,17], the coarse needlelike primary CaMgSn phases and the feather-like eutectic CaMgSn phases are clearly observed in the ternary Mg-3Sn-2Ca alloy (see Figs. 4 and 5a and b).…”
Section: Resultssupporting
confidence: 82%
“…The difference in the tensile properties of the experimental alloys with and without adding Gd is possibly related to other reasons. According to the previous investigations [6,9,17], the coarse needle-like primary CaMgSn phases in the Mg-Sn-Ca alloys will give a detrimental effect on the mechanical properties because the cracks can easily nucleate along the interface between the primary CaMgSn particle and ␣-Mg matrix. Therefore, it is preliminarily inferred that the improvement of the tensile properties for the Gd-containing Mg-3Sn-2Ca alloys is possibly related to the modification and/or refinement of the primary CaMgSn phases.…”
Section: Effects On Mechanical Propertiesmentioning
confidence: 97%
“…Due to the detrimental Mg 17 Al 12 phase formation in Mg-Al based systems, the research focus on developing new creep resistant Mg alloys has now shifted to Mg alloys not containing any Al. Some alloy systems that possess high creep resistance are Mg-Sc-Mn [14,15], Mg-YNd-Mn [15,16], Mg-Zn-RE [11], Mg-Mn-Ce [17][18][19], Mg-Ca-Zn [20] and Mg-Sn-Ca [21].…”
Section: Introductionmentioning
confidence: 99%
“…A primary CaMgSn and SrMgSn phase grows with a rod-like shape in the liquid melt at the initial solidification stage. In general, when the difference in composition between the primary and other eutectic phase is high enough, a solute depleted zone forms easily around the primary solidification phase [22]. SEM-EDS and XRD showed that they form in the Mg-Sn-Ca and Mg-Sn-Sr containing alloys, respectively.…”
Section: Resultsmentioning
confidence: 99%